Impact of pharmacokinetics to reduce bleeding in a cohort of patients with severe hemophilia A in a personalized comprehensive management program - Samuel sarmiento Doncel (PAGEPress Publications, 2021)
Introduction: In recent decades, hemophilia A treatment has been focused on body weight, without taking pharmacokinetic parameters into account. Previous research has shown that the individual pharmacokinetic response is more effective in predicting the required dose of clotting factor. We want to evaluate the impact on reducing the frequency of bleeding in patients treated with recombinant factor VIII, based on a personalized comprehensive management program.